2015
DOI: 10.1038/nature14898
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional plasticity promotes primary and acquired resistance to BET inhibition

Abstract: Summary Following the discovery of BRD4 as a non-oncogene addiction target in acute myeloid leukemia (AML)1,2, BET inhibitors are being explored as promising therapeutic avenue in numerous cancers3–5. While clinical trials have reported single-agent activity in advanced hematologic malignancies6, mechanisms determining the response to BET inhibition remain poorly understood. To identify factors involved in primary and acquired BET resistance in leukemia, we performed a chromatin-focused RNAi screen in a sensit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

15
413
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 441 publications
(430 citation statements)
references
References 55 publications
15
413
1
1
Order By: Relevance
“…S8D) in line with H23 cells undergoing apoptosis and slower cell proliferation rate (Figure 5(b)). The main components of canonical Wnt/β-catenin signaling are reported to be modulated by JQ1 [6,29,30] and in H23 cells, WNT2, WNT5A, and the mediator of Wnt signaling (LEF1 and TCF genes) were downregulated, while β-catenin encoded by CTNNB1 was only slightly affected (Fig. S8B).…”
Section: Resultsmentioning
confidence: 99%
“…S8D) in line with H23 cells undergoing apoptosis and slower cell proliferation rate (Figure 5(b)). The main components of canonical Wnt/β-catenin signaling are reported to be modulated by JQ1 [6,29,30] and in H23 cells, WNT2, WNT5A, and the mediator of Wnt signaling (LEF1 and TCF genes) were downregulated, while β-catenin encoded by CTNNB1 was only slightly affected (Fig. S8B).…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, it has been shown that one resistance mechanism was associated with the upregulation of WNT signaling, and this process is needed to restore the expression of important drivers initially downregulated by BET-I, including MYC (51). Consistently, in cell-based PDAC models, activation of the WNT signaling pathway confers resistance, whereas WNT inhibition was synergistic with the JQ1 response (51).…”
Section: Targeting Myc Indirectlymentioning
confidence: 57%
“…The context specificity is not only observed between different tumors, but also within a given tumor entity. In line, transcriptome profiles of BET-I-treated cells demonstrated a dramatic heterogeneous response, even in tumors of the same entity (51). Furthermore, in breast cancer models, the regulation of MYC mRNA in response to BET-I does not discriminate between sensitive and insensitive lines, further pointing to the highly context-dependent function of MYC in the response toward these kinds of drugs (52).…”
Section: Targeting Myc Indirectlymentioning
confidence: 61%
“…While Rathert et al [7] did not find major differences in gene expression between sensitive and resistant clones upon short-term treatment with JQ1, resistant clones over time displayed divergent gene expression patterns including the restoration of multiple crucial transcripts such as Tifab and Myc. Rebound expression of Myc was also a feature of resistant human AML cell lines versus sensitive lines despite initial loss in both.…”
mentioning
confidence: 98%
“…In a separate study that focused on intrinsic resistance, Rathert and colleagues [7] employed a screen against an shRNA library of 626 chromatin modifiers, aiming to identify crucial factors that confer BET inhibitor resistance to the murine MLL-AF9;Nras G12D model of AML. Cells expressing shRNAs targeting Suz12, Psip12, and Dnmt3 showed robust resistance to JQ1 treatment.…”
mentioning
confidence: 99%